THE DRIVERS OF COMPANY CAPITAL STRUCTURE - Melati; Elwisam; Suadi Sapta Putra; Kumba Digdowiseiso; Yulita (CV. RADJA PUBLIKA, 2024)
Companies have a demand to comprehend the factors that impact their choice between equity and debt capital. The objective of this research is to condense and combine existing discoveries pertaining to the factors that influence a company's capital structure. The study employed the Systematic Literature Review (SLR) method, which facilitates meticulous, discerning, and well-documented searches of literature to obtain more precise and all-encompassing insights. The research findings indicate that business risk, profitability, company size, and company growth exert a substantial influence on the capital structure policy. Nevertheless, certain factors, such as asset structure, non-debt tax shield, and uniqueness, do not consistently demonstrate an influence. The discussion emphasizes the intricacy of the connections between these variables and the necessity of adopting a contextual approach when managing capital structure. To achieve long-term financial goals, it is crucial to have a comprehensive comprehension of the business context and company characteristics when making decisions about capital structure.